Nano-hydroxyapatite-coated metal-ceramic composite of iron-tricalcium phosphate: Improving the surface wettability, adhesion and proliferation of mesenchymal stem cells in vitro; Colloids and Surfaces B: Biointerfaces; Vol. 135, iss. 1 - Surmeneva M. A. Maria Alexandrovna; Kleinhans C. Claudia; Vacun G. Gabriele; Kluger P. J. Petra Juliane; Schoenhaar V. Veronika; Mueller M. Michaela; Hein S. B. Sebastian Boris; Wittmar A. Alexandra; Ulbricht M. Mathias; Prymak O. Oleg; Oehr C. Christian; Surmenev R. A. Roman Anatolievich (2015, 2015)
Title screen